Ankle Range of Motion after Total Ankle Replacement with and without Heel Cord Lengthening - Roxa Ruiz MD; Nicola Krähenbühl MD; Alexej Barg MD; Beat Hintermann MD (Foot & Ankle Orthopaedics, 2019)
Category: Ankle, Ankle Arthritis Introduction/Purpose: Though total ankle replacement (TAR) has become a well-accepted alternative to fusion for treatment of end-stage ankle osteoarthritis (OA), controversy still exists regarding the appropriate indications. In 80% of the cases, trauma accounts for the primary cause of end-stage ankle OA. In these cases, the soft tissue conditions are often poor and the remaining ankle range of motion (ROM) limited. Additionally, performing a heel cord lengthening (HCL) should theoretically increase ankle ROM. However, it remains unclear to which extent a preoperative stiff ankle can become mobile after a TAR, with or without a HCL. The purpose of this study was to assess the gained ROM after TAR in end-stage ankle OA, and whether it is beneficial for patients who additionally underwent a HCL. Methods: Out of 605 primary TAR performed at our institution between 2006 and 2015, 288 ankles (280 patients; age 64.1 [39 – 88]; male, 151; female, 129) were identified with a neutral hindfoot alignment, no degenerative changes or previous fusions of adjacent joints, and no previous ligament reconstruction and tendon transfers at time of TAR. Medial and lateral gutter debridement as well as a complete posterior capsule resection was performed before the prosthesis was inserted. The ankle was then gradually mobilized into dorsiflexion. If a minimum of 10° dorsiflexion could not be obtained, HCL was performed (percutaneous triple hemisection). Postoperatively, the ankle was protected by a walker and weight-bearing was permitted as tolerated. ROM was determined during weight-bearing with the use of a goniometer preoperatively and 2-years postoperatively. Pearson correlation analysis and paired t-test were used for statistical analysis. Results: Out of 288 ankles, 41 (14.2%) underwent additional HCL. Preoperative ROM correlated with the ROM 2-years after TAR, independent whether a HCL was performed (p < 0.01) or not (p < 0.01). ROM for the ankles where no HCL was performed was 35° preoperatively and 34° 2-years postoperatively. For the ankles in which a HCL was performed, it was 28° preoperatively and 28° 2-years postoperatively. Pearson correlation analysis showed that patients with a low ROM preoperatively tended to get more motion after TAR, whereas patients with an extensive preoperative ROM even lost some motion after receiving a TAR system (Figure 1). Conclusion: The data suggests that a HCL procedure has little potential to ameliorate a preoperative low ROM. A TAR system however, may help increase the ROM in patients with little preoperative ROM while in patients with extensive preoperative ROM it may even cause a loss of ROM. The data further suggests that the heel cord contracture is not the only cause of limited motion in end-stage ankle OA, and that whether TAR nor TAR in combination with HCL should be performed with the goal of gaining ROM for the treatment of end-stage OA.